Osteoarthritis in two marine mammals and 22 land mammals: learning from skeletal remains - Korakot Nganvongpanit (2018)
© 2017 Anatomical Society The occurrence of osteoarthritis (OA) in marine mammals is still questionable. Here we investigated the prevalence of OA in marine (dolphin and dugong) and terrestrial mammals (Asian elephant, Asiatic buffalo, camel, cat, cattle, deer, dog, domestic goat, horse, human, hyena, impala, lion, Malayan tapir, Assam macaque, mule, pig, rabbit, red kangaroo, sheep, tiger and waterbuck). Skeletal remains obtained from five institutes were used as subjects; a total of 45 different parts (locations) of bones were observed for OA lesions. The prevalence of OA was reported as number of OA lesions/total number of bones. Our results revealed that the presence of OA in marine species (dolphin and dugong) was 2.44% and 3.33%, respectively. In dolphins, the highest OA occurrence was on the left and right humeral trochlea, with 13.68% and 12.63%, respectively, while the highest number of OA lesions in dugongs was on the lumbar vertebrae (8.79%). No significant difference (P > 0.05) in the prevalence of OA between sexes in dolphins and dugongs was observed, but we found a significant difference (P < 0.05) in 24 bone locations of human bones, which had the highest OA prevalence (48.93%), followed by dogs (3.94%). In conclusion, OA can occur in marine mammals, similar to terrestrial mammals, even though their natural habitat is the ocean.